The participation of children and adolescents in spaces of social control: the experience of national conferences (Emancipação, 2020)
Children and adolescents’ citizen participation is a human right, made explicit in international and national norms. The participation in the political-institutional field, especially through the National Conferences on the Rights of Children and Adolescents (CNDCAs), took place inaccurately and gradually, but with relative advances throughout its editions. The results of the documentary research point to two participatory cycles of children and adolescents in the CNDCAs: the 1st cycle, in the period from 1995 to 2007, when seven editions of the CNDCAs were held; and the 2nd cycle, between 2009 and 2016, when three editions of the Conferences were held. The historical procedurality of this participation culminated with the inclusion of the axis "Protagonism and participation of children and adolescents" in the Decennial Plan for the Human Rights of Children and Adolescents. The data suggest that as of the 10th Conference we may have started the 3rd cycle of this participation.
Keywords: Child and Adolescent. Citizen participation. Conferences.